2001
DOI: 10.1007/s005950170005
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Immediate Enteral Nutrition After Esophageal Cancer Surgery

Abstract: This study was conducted to determine the effects of immediate enteral nutrition (EN) on nutritional status, immunological competence, and the suppression of excessive inflammatory responses in patients following esophageal cancer surgery. Twenty-four patients who underwent the same elective operation for thoracic esophageal carcinoma were randomized into an immediate enteral nutrition (IEN) group who received EN from postoperative day (POD) 1 and a parenteral nutrition (PAN) group. Both groups received compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 36 publications
0
62
0
3
Order By: Relevance
“…Performing a power calculation for their primary outcomes would help identify such potential errors but only one of the studies performed such a calculation (Cooper et al, 2006), suggesting that 40-60 patients and 100 patients per arm will be required to show a significant difference in mortality and 30 day complications, respectively. Shiraishi et al (2005) and Aiko et al (2001), attempt to examine the benefit of enteral feeding in patients undergoing oesophagectomy. As above, both studies carry a risk of bias with no reported randomisation technique on a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Performing a power calculation for their primary outcomes would help identify such potential errors but only one of the studies performed such a calculation (Cooper et al, 2006), suggesting that 40-60 patients and 100 patients per arm will be required to show a significant difference in mortality and 30 day complications, respectively. Shiraishi et al (2005) and Aiko et al (2001), attempt to examine the benefit of enteral feeding in patients undergoing oesophagectomy. As above, both studies carry a risk of bias with no reported randomisation technique on a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…As above, both studies carry a risk of bias with no reported randomisation technique on a small number of patients. Aiko et al (2001) combine parenteral and enteral feeding and compare them to parenteral feeding alone. As it may be possible to attribute central line complications to the enteral feeding route in the combined group, it is difficult to assess the impact that enteral feeding has got.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, reports of the effects of postoperative early enteral nutrition (EEN) specifically in patients undergoing esophagectomy were limited [14,22,23]. Furthermore, most clinical studies did not compare enteral nutrition and total parenteral nutrition in a randomized fashion [14,22,24].…”
Section: Discussionmentioning
confidence: 99%